On the preliminary shape design of axisymmetric twin-web turbine discs considering the burst speed constraint. Issue 12 (2nd December 2022) - Wang, Bo; Wang, Guangming; Huang, Lei; Xu, Shengli; Tian, Kuo
Abstract : In this article, a topology optimization method is proposed to obtain a new preliminary shape design of the twin-web turbine disc considering the burst speed constraint. The burst speed constraint is converted to the constraints on the averaged hoop stress and the maximum averaged radial stress. The linear density filter and Heaviside projection are employed to prevent the mesh dependency and chequerboard pattern and ensure distinct solid/void interfaces in the optimization result. The geometric extraction is easily implemented using the least square fitting with B-spline method. Through illustrative examples, the importance of considering the burst speed constraint in the design of turbine disc is verified, which contributes towards obtaining a safer design at the preliminary design stage. The effectiveness of the proposed method in obtaining a lighter preliminary twin-web turbine disc design is also demonstrated compared with the parametric optimization method.